RESPON TANAMAN LIDAH BUAYA (Aloe vera chinensis) TERHADAP PEMBERIAN KALIUM DAN PUPUK KANDANG SAPI - Sari, Ratika '; ', Islan '; ', Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Aloe vera chinensis is a tropical plant which has potential to developed in Indonesia. The qualified of aloe vera’s leaf is determine by quality of seed which used. The effort to increase the productivity of aloe vera’s leaf need to considered is soil fertility. The research aims to observe the response of aloe vera chinensis to interaction of potassium and cow manure and obtain the best dose of potassium and cow manure. This research has been conducted at the experimental farm of Agricultural Faculty Riau University on June to September 2015.The research was carried out experimentally using a randomized block design (RBD) consisted of2 factors and 3 replications. The first factor was KCl doses (0, 5, 10 and 15 g KCl/plant), the second factor doses of cow manure (100, 200 and 300 g cow manure/plant). Data obtained were statistically analyzed using analysis of variance andDuncan’s New Multiple Range Test (DNMRT) at 5%. The results showed that application of 15 g KCl/plant and 200 g cow manure/plant able to support the aloe vera’s growth. Keywords : Aloe vera, potassium, cow manure.